Предмет: Алгебра,
автор: natalyachavdar
Решите уравнение: (x-4)(x+4)-6x=(x-2)*
* - во второй степени
Ответы
Автор ответа:
0
(х-4)(х+4)-6х=(х-2)²
х²-16-6х=х²-4х+4
х²-х²-6х+4х=20
-2х=20
х=-10
(запомни формулы сокращенного умножения)
(a-b)(a+b)=a²-b²
(a-b)²=a²-2ab+b²
х²-16-6х=х²-4х+4
х²-х²-6х+4х=20
-2х=20
х=-10
(запомни формулы сокращенного умножения)
(a-b)(a+b)=a²-b²
(a-b)²=a²-2ab+b²
Похожие вопросы
Предмет: Математика,
автор: aldiark861
Предмет: Английский язык,
автор: Radle8
Предмет: Русский язык,
автор: aiymmyrzakhmetova83
Предмет: Обществознание,
автор: Аноним
Предмет: Физика,
автор: maria11111111